Dose individualisation in oncology using chemotherapy‐induced neutropenia: Example of docetaxel in non‐small cell lung cancer patients. Issue 4 (19th December 2020) - Lombard, Aurélie; Mistry, Hitesh; Aarons, Leon; Ogungbenro, Kayode
Abstract : Aims: Chemotherapy‐induced neutropenia has been associated with an increase in overall survival in non‐small cell lung cancer patients. Therefore, neutrophil counts could be an interesting biomarker for drug efficacy as well as linked directly to toxicity. For drugs where neutropenia is dose limiting, neutrophil counts might be used for monitoring drug effect and for dosing optimisation. Methods: The relationship between drug effect on the first cycle neutrophil counts and patient survival was explored in a Phase III clinical trial where patients with non‐small cell lung cancer were treated with docetaxel. Once the association has been established, dosing optimisation was performed for patients with severe toxicities (neutropenia) without compromising drug efficacy (overall survival). Results: After taking into account baseline prognostic factors, such as Eastern Cooperative Oncology Group performance status, smoking status, liver metastasis, tumour burden, neutrophil counts and albumin levels, a model‐predicted drug effect on the first cycle neutrophil counts was strongly associated with patient survival ( P = .005). Utilising this relationship in a dose optimisation algorithm, 194 out of 366 patients would have benefited from a dose reduction after the first cycle of docetaxel. The simulated 1‐year survival probabilities associated with the original dose and the individualised dose were not different. Conclusion: The strong relationship between drug effect on the first cycle neutrophil counts and patient survival suggests that this variable could be used to individualise dosing, possibly without needing pharmacokinetic samples. The algorithm highlights that doses could be reduced in case of severe haematological toxicities without compromising drug efficacy.